Liquid-Based Cytology of the Cerebrospinal Fluid in a Case of Cryptococcal Meningitis - Jiwoon Choi; Se Hoon Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Cryptococcus neoformans is the most common microorganism found in cerebrospinal fluid (CSF) cytology and causes life-threatening infections in immunocompromised hosts. Although its cytomorphologic features in conventional smear cytology have been well described, those in liquid-based cytology have rarely been. A 73-year-old woman with diffuse large B-cell lymphoma presented with mental confusion and a spiking fever. To rule out infectious conditions, CSF examination was performed. A cytology slide that was prepared using the ThinPrep method showed numerous spherical yeast-form organisms with diameters of 4-11 μm and thick capsules. Occasional asymmetrical, narrow-based budding but no true hyphae or pseudohyphae were observed. Gomori methenamine silver staining was positive. Cryptococcosis was confirmed in blood and CSF through the cryptococcal antigen test and culture. Liquid-based cytology allows for a clean background and additional slides for ancillary testing, facilitating the detection of microorganisms in CSF specimens, particularly when the number of organisms is small.